Percepção da alteração da atratividade facial em indivíduos submetidos à cirurgia ortognática - Araujo Neto, Gentil Homem de (2006)
The aim of this study was to analyze whether an orthognathic surgery could change the face profile attractiveness of individuals with dentofacial deformities. Fifty profile photographs of 05 individuals were classified into Standard II, 14 Standard III and 06 Long Face Standard, after that the submitted the orthognathic surgery. A group of evaluators, 05 plastic surgeons, 05 maxillofacial surgeons, 05 orthodontists and 05 laypeople, analyzed the facial attractiveness of the patients before and after surgery. The analysis was performed by the observation of presurgical and postsurgical photographs from the face profile of all patients, randomly arranged in an album. The evaluators classified the patients according to the following scores: aesthetic pleasant (scores 7, 8 and 9); aesthetic acceptable (scores 4, 5 and 6) and aesthetic unpleasant (scores 1, 2 and 3). The Wilcoxon test (p<0.05) demonstrated that the evaluators noted an improvement of the face attractiveness of all individuals and in 23 individuals significant differences were perceived between presurgical and postsurgical photographs. The age and gender of the patients had not an influence in the results. The lips, the chin and the chin-neck line were the most important aspects used to justify the unpleasant aesthetic appearance. According to the results of this study and the employed methodology it can be concluded that face profile changes by orthognathic surgery improved the attractiveness of the individuals with dentofacial deformities.